Pengaruh Gamifikasi Terhadap Repurchase Intention Pada Aplikasi ByU - Indriani, Arsita; Vania, Amelindha (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2025)
This study aims to analyze the impact of gamification on customer repurchase decisions. Using linear regression methods, the research involved 50 respondents who are ByU users in Malang City, focusing on gamification elements. The analysis results indicate that gamification has a significant positive effect on repurchase, with a regression coefficient of 0.817 and a significance level of p < 0.001. Additionally, ANOVA analysis revealed that the developed model substantially explains the variability in repurchase (F = 184.228, p < 0.001). These findings suggest that implementing gamification elements in marketing strategies can enhance customer engagement and loyalty. While this study provides valuable insights, limitations related to sample size and research design indicate the need for further studies to deepen the understanding of this dynamic. This research is expected to serve as a reference for companies in designing effective strategies to improve customer retention through gamification.